Hubungan Air Susu Ibu (ASI) Eksklusif dengan Kejadian Stunting pada Baduta di Kota Manado - Pratama, Fauzan I.; Mayulu, Nelly; Kawengian, Shirley E. S. (e-Biomedik, 2019)
Abstract: Stunting is caused by many factors, including not getting exclusive breastfeeding, namely breastfeeding without any other additional foods and drinks at the age of zero months to 6 months. This study was aimed to determine the relationship between exclusive breastfeeding and the incidence of stunting among children under two years old in Manado. This was an observational and analytical study with a case control design (retrospective). The chi-square test (x2) at the 95% of significancy was used to obtain the relationship between exclusive breastfeeding and the occurrence of stunting data. Furthermore, to determine the magnitude of the problem of children who did not get exclusive breastfeeding against the incidence of stunting, the odds ratio (OR) was calculated. The results obtained a p-value of 0.02 (<Î±=0.05) and an odds ratio (OR) of 2.65, which meant that there was a relationship between exclusive breastfeeding and the incidence of stunting. In conclusion, there was a significant relationship between exclusive breastfeeding and stunting incidence among children under two years old in Manado.Keywords: stunting, exclusive breastfeeding, children under two years oldÂ Abstrak : Stunting disebabkan oleh banyak faktor, di antaranya tidak mendapatkan ASI ekslusif, yakni pemberian ASI tanpa makanan dan minuman lain pada usia nol bulan sampai 6 bulan. Penelitian ini bertujuan untuk mengetahui hubungan antara ASI ekslusif dengan kejadian stunting pada anak usia bawah dua tahun (baduta) di Kota Manado. Jenis penelitian ialah observasional analitik dengan rancangan case control (retrospektif). Uji statistik terhadap hubungan meng-gunakan uji chi-square (x2) pada tingkat kemaknaan 95%. Untuk mengetahui besarnya risiko anak yang tidak mendapatkan ASI ekslusif terhadap kejadian stunting, dilakukan penghitungan odds ratio (OR). Hasil uji chi-square mendapatkan nilai p sebesar 0,02 (<Î±=0,05) yang berarti terdapat hubungan bermakna antara pemberian ASI ekslusif dengan kejadian stunting dengan nilai Odds Ratio (OR) sebesar 2,65. Simpulan penelitian ini ialah terdapat hubungan bermakna antara pemberian ASI ekslusif dengan kejadian stunting pada anak baduta di Kota Manado.Kata kunci: stunting, ASI eksusif, baduta